LncRNA MEG3: Potential stock for precision treatment of cardiovascular diseases - Li, Zining; Gao, Jialiang; Sun, Di; Jiao, Qian; Ma, Jing; Cui, Weilu; Lou, Yuqing; Xu, Fan; Li, Shanshan; Li, Haixia (Frontiers in Pharmacology, 2022)
The prevalence and mortality rates of cardiovascular diseases are increasing, and new treatment strategies are urgently needed. From the perspective of basic pathogenesis, the occurrence and development of cardiovascular diseases are related to inflammation, apoptosis, fibrosis and autophagy of cardiomyocytes, endothelial cells and other related cells. The involvement of maternally expressed gene 3 (MEG3) in human disease processes has been increasingly reported. P53 and PI3K/Akt are important pathways by which MEG3 participates in regulating cell apoptosis. MEG3 directly or competitively binds with miRNA to participate in apoptosis, inflammation, oxidative stress, endoplasmic reticulum stress, EMT and other processes. LncRNA MEG3 is mainly involved in malignant tumors, metabolic diseases, immune system diseases, cardiovascular and cerebrovascular diseases, etc. LncRNA MEG3 has a variety of pathological effects in cardiomyocytes, fibroblasts and endothelial cells and has great clinical application potential in the prevention and treatment of AS, MIRI, hypertension and HF. This paper will review the research progress of MEG3 in the aspects of mechanism of action, other systemic diseases and cardiovascular diseases, and point out its great potential in the prevention and treatment of cardiovascular diseases. lncRNAs also play a role in endothelial cells. In addition, lncRNA MEG3 has shown biomarker value, prognostic value and therapeutic response measurement in tumor diseases. We boldly speculate that MEG3 will play a role in the emerging discipline of tumor heart disease.